Development of e-Resto Innovation To Strengthen Cross-Sectoral Collaboration Commitment In Efforts To Control Child Wasting - Suhron, M; Suryani, Lilik; Fitriah, Fitriah; Susanti, Eny (Universitas Tribhuwana Tunggadewi, 2026)
Wasting among children remains a major global public health problem. Strengthening cross-sector collaboration is considered an effective approach to address this issue. This study aimed to analyze the development of the e-RESTO Balita innovation in strengthening cross-sector collaboration commitment in efforts to control wasting. This study employed a quantitative pre–post test design involving 20 participants representing cross-sector stakeholders in the Banyuanyar Community Health Center work area. Data were collected using questionnaires measuring application development and cross-sector collaboration commitment, supported by interviews. Statistical analysis was performed using the Wilcoxon test. The findings showed that the development of the e-RESTO Balita application significantly improved and strengthened cross-sector collaboration commitment in efforts to control wasting (p 0.05). The development of the e-RESTO Balita innovation was effective in enhancing cross-sector collaboration in the management of child malnutrition. Future development of the system is recommended through the integration of a more user-friendly Android-based application to facilitate faster and easier access for stakeholders.